Use of Antiseptics and Antibiotics in Periimplant - Yuldashev Azizjon Muratbayevich (Zien Journals, 2022)
Effective use of antibiotics is also recommended in orthopedic and traumatic surgery to prevent the spread of infection. In addition to this established system, a new approach to antibiotic prophylaxis can reduce infection. Antimicrobial prophylaxis is especially important in cases of open fractures.
Keywords: reduce; Antimicrobial; fractures; prophylaxis